Facial profile esthetics in operated children with bilateral cleft lip and palate - Rita de Cássia Moura Carvalho Lauris; Leopoldino Capelozza Filho; Louise Resti Calil; José Roberto Pereira Lauris; Guilherme Janson; Daniela Gamba Garib
ABSTRACT Objective: The aim of this study was to evaluate the facial profile esthetics of rehabilitated children with complete bilateral cleft lip and palate (BCLP), comparing the judgment of professionals related and not related to cleft rehabilitation and laypersons. Methods: Thirty children in the mixed dentition (24 male; 6 female) with a mean age of 7.8 years were evaluated using facial profile photographs by 25 examiners: 5 orthodontists and 5 plastic surgeons with experience in cleft care, 5 orthodontists and 5 plastic surgeons without experience in oral cleft rehabilitation and 5 graduated laymen. Their facial profiles were classified into esthetically unpleasant (grade 1 to 3), esthetically acceptable (grade 4 to 6), and esthetically pleasant (grade 7 to 9). Intraexaminer and interexaminer errors were evaluated using Spearman correlation coefficient and Kendall's test, respectively. Inter-rater differences were analyzed using Friedman test and Student-Newman-Keuls test for multiple comparisons. Results: Orthodontists dealing with oral clefts rehabilitation considered the majority of the sample as esthetically pleasant. Plastic surgeons of the cleft team and laypersons classified most of the sample as esthetically acceptable. Most of the orthodontists and plastic surgeons not related to cleft care evaluated the facial profile as esthetically unpleasant. The structures associated to unpleasant profiles were the nose, the midface and the upper lip. Conclusions: The facial profile of children with BCLP was classified as esthetically acceptable by laypersons. Professionals related to cleft rehabilitation were more lenient and those not related to cleft care were stricter to facial esthetics than laypersons.